THE GENRE OF CYCLICAL PIANO PAINTINGS IN THE WORKS OF MUSTAFO BAFOEV (ON THE EXAMPLE OF “FIVE MUSICAL PAINTINGS BASED ON READING ALPAMYSH”) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The Uzbek people have created a unique musical culture, and the art of piano occupies an important place in it, attracting the attention of both performers and researchers. Particular attention is paid to the genre of cyclic piano picture, which allows composers to convey orchestral picturesqueness in the sounds of one instrument. This genre reflects the revival of neo-romanticism, artistic picturesqueness and the Uzbek worldview. The article is devoted to the genre of cyclic piano picture in the works of Mustafa Bafoev, in particular his work «Five Musical Pictures Based on the Reading of Alpomysh». The author examines the stylistic features, texture and thematic features of the work, and also summarizes the evolution of the genre in the music of Uzbekistan. For the first time, the term «isoteria» is introduced, explaining the influence of opera art on instrumental music. The article presents a historical and comparative analysis, an attempt to classify the cyclic piano picture in the works of Uzbek composers. New sound production techniques and images of Uzbek folk instruments such as dutar and doira have been discovered. The study is based on the work of musicologists and contributes to the further development of the genre.
Keywords: genre, cyclicality, picture artistic, creativity, composer, programmatic, dastan, piano, cycle.